Palliative care in end-stage valvular heart disease. Issue 16 (26th July 2017) - Steiner, Jill M; Cooper, Stephanie; Kirkpatrick, James N
Abstract : Valvular heart disease (VHD), particularly aortic valve disease, is prevalent with increasing incidence. When surgery is not possible, or when risks outweigh benefits, percutaneous treatment options may offer effective alternatives. However, procedures may not always go as planned, and frail patients or those whose symptoms are caused by other comorbidities may not benefit from valve intervention at all. Significant effort should be made to assess frailty, comorbidities and patient goals prior to intervention. Palliative care (PC) should play a critical role in the care of patients with severe valve disease. PC is specialised medical care that aims to optimise health-related quality of life by managing symptoms and clarifying patient values and goals of care. It should be implemented at the time of diagnosis and continue throughout the disease course. Because of the paucity of studies dedicated to the provision of PC to patients with advanced VHD, further research is needed.